2008
DOI: 10.1086/587678
|View full text |Cite
|
Sign up to set email alerts
|

Galaxy Clusters in the Line of Sight to Background Quasars. I. Survey Design and Incidence of MgiiAbsorbers at Cluster Redshifts

Abstract: Quasar absorption line systems are redshift-independent sensitive mass tracers. Here we describe the first optical survey of absorption systems associated with galaxy clusters at z = 0.3 − 0.9. We have cross-correlated quasars from the third data release of the Sloan Digital Sky Survey with high-redshift cluster/group candidates from the Red-Sequence Cluster Survey. In a common field of ≈ 20 square degrees, we have found 442 quasar-cluster pairs for which the Mg II λλ2796, 2803Å doublet might be detected at a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
63
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(67 citation statements)
references
References 84 publications
4
63
0
Order By: Relevance
“…A powerful observational technique is the exploitation of continuum‐bright background sources to search for spectroscopic evidence of absorption of continuum light by intervening intergalactic/intracluster material. For example, Lopez et al (2008) present a study of 442 cluster–quasar pairs (sightlines) within the Red Sequence Cluster Survey (RCS; Gladders & Yee 2000, 2005) where the Mg ii λλ2796, 2803 doublet could be detected at 0.3 < z < 0.9. The study of the distribution of the equivalent width of absorption‐line systems within clusters could provide a means of studying environmental effects such as gas‐stripping in dense environment.…”
Section: Detection Of Clusters In the Sloan Digital Sky Survey Equamentioning
confidence: 99%
“…A powerful observational technique is the exploitation of continuum‐bright background sources to search for spectroscopic evidence of absorption of continuum light by intervening intergalactic/intracluster material. For example, Lopez et al (2008) present a study of 442 cluster–quasar pairs (sightlines) within the Red Sequence Cluster Survey (RCS; Gladders & Yee 2000, 2005) where the Mg ii λλ2796, 2803 doublet could be detected at 0.3 < z < 0.9. The study of the distribution of the equivalent width of absorption‐line systems within clusters could provide a means of studying environmental effects such as gas‐stripping in dense environment.…”
Section: Detection Of Clusters In the Sloan Digital Sky Survey Equamentioning
confidence: 99%
“…Borgani et al ; Padilla et al ) and observed (e.g. Lewis et al ; Lopez et al ; Padilla, Lambas & González ) to have non‐negligible effects on the gas and galaxy properties. Given that baryonic matter is expected to fall into the considerably deeper gravitational potentials of dark matter, the IGM gas and galaxies are expected to be predominantly found at such locations forming the so‐called ‘cosmic web’ (Bond, Kofman & Pogosyan ).…”
Section: Introductionmentioning
confidence: 96%
“…In contrast, the d N /d z of weak Mg ii systems [ W r (2796) < 0.3Å] in clusters is consistent with those derived from environmentally unbiased samples. Lopez et al (2008) argue that the detected over‐abundance of strong systems is a result of the over‐density of galaxies in a cluster region. The lack of an over‐abundance of weak systems may imply that they were destroyed by the cluster environment.…”
Section: Introductionmentioning
confidence: 99%
“…Padilla et al (2009) modelled these results and found environmental evidence of truncated Mg ii halo sizes as a function of cluster radii. Their models require a median Mg ii halo size of r < 10 h −1 kpc, compared to 35–85 h −1 kpc for field galaxies, in order to reproduce the observed absorption‐line statistics of Lopez et al (2008). These X‐ray‐selected clusters represent more extreme environments than in galaxy groups where the majority of galaxies reside.…”
Section: Introductionmentioning
confidence: 99%